2021
DOI: 10.1016/j.bpj.2021.04.022
|View full text |Cite
|
Sign up to set email alerts
|

DNA looping by protamine follows a nonuniform spatial distribution

Abstract: DNA looping plays an important role in cells in both regulating and protecting the genome. Often, studies of looping focus on looping by prokaryotic transcription factors like lac repressor or by structural maintenance of chromosomes proteins such as condensin. Here, however, we are interested in a different looping method whereby condensing agents (charge Rþ3) such as protamine proteins neutralize the DNA, causing it to form loops and toroids. We considered two previously proposed mechanisms for DNA looping b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Recent studies using tethered particle motion assays and AFM found that salmon protamine uses a multi-step process, forming multiple independent loops of a roughly defined diameter that come together before forming a larger toroidal structure ( 137 ). Furthermore, the formation of these structures relies on protamine binding-and-bending the DNA, whereby multiple protamine molecules bind locally to a DNA segment to induce bending of the DNA filament to form loops ( 138 ). These data are in agreement with previous studies that identified loops formed by sperm DNA in vivo ( 119 , 121 , 124 ) as well as our recent EMSA and single molecule DNA curtain assays, which suggest that large-scale genome compaction by protamines is achieved by protamine protein cooperativity ( 95 ).…”
Section: Something Old Something New: Experimental Approaches To Unde...mentioning
confidence: 99%
“…Recent studies using tethered particle motion assays and AFM found that salmon protamine uses a multi-step process, forming multiple independent loops of a roughly defined diameter that come together before forming a larger toroidal structure ( 137 ). Furthermore, the formation of these structures relies on protamine binding-and-bending the DNA, whereby multiple protamine molecules bind locally to a DNA segment to induce bending of the DNA filament to form loops ( 138 ). These data are in agreement with previous studies that identified loops formed by sperm DNA in vivo ( 119 , 121 , 124 ) as well as our recent EMSA and single molecule DNA curtain assays, which suggest that large-scale genome compaction by protamines is achieved by protamine protein cooperativity ( 95 ).…”
Section: Something Old Something New: Experimental Approaches To Unde...mentioning
confidence: 99%
“…14 Additionally, it was reported that chromosomal protein could help doublestranded DNA fold into loops. 15,16 These important pioneering works are intriguing and are excellent examples of artificial nanoarchitectures arising from DNA interactions with natural biomolecules. Nonetheless, most of the above-mentioned reports were proof-of-concept studies and limited to in vitro validation.…”
Section: Introductionmentioning
confidence: 99%